Analytical Hierarchy Process (AHP), Fuzzy AHP, and TOPSIS for Determining Bridge Maintenance Priority Scale in Banjarsari, Surakarta - Ayu Intan Nurani; Astri Tamara Pramudyaningrum; Shofie Rizqi Fadhila; Senot Sangadji; Widi Hartono (Universitas Sebelas Maret, 2017)
Data on 2015 [9] show that less than 50 percent of provincial and local level bridges in Central Java are in good condition. In the other hand, it has been reported that local bridges in the city of Surakarta have been deteriorated and damaged. The maintenance and rehabilitation action often done based solely on incidental reports without systematic planning. Analytical Hierarchy Process, Fuzzy Analytical Hierarchy Process, and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) were used to compare the priority scale of bridge management in Kecamatan (District) Banjarsari, Surakarta. Bridge Management System 1993 (BMS 1993) standard was used to quantify bridge damage condition by means of direct visual observation. Scores used in this 3 different analysis were determined by comparing aforementioned 2 criteria and 9 sub criteria. Accordingly, criteria and subcriteria defined in this paper were based on the standard. The criteria employed were bridge damage condition and average daily traffic (ADT). Bridge condition criteria were then divided further into sub criteria; i.e. river stream, safety support building, foundation, pier, girder system, parapet, floor system, expansion joint, and other property. From 11 bridges considered in this study, Maris Bridge has the highest pirority determined in 3 different methods. AHP and TOPSIS methods show Ringin Semar Bridge the lowest priority to maintain. On the other hand, Fuzzy AHP determines Balapan Bridge as the lowest order. Keyword: Bridge Management, BMS 1993, AHP, FAHP, TOPSIS.